2018
DOI: 10.14359/51702372
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Flexural Reinforced Concrete Columns with Corroded Reinforcement

Abstract: This paper presents an experimental study carried out on eight full-scale uncorroded and corroded reinforced concrete columns that were subjected to simulated seismic loading to investigate the effects of reinforcement corrosion on the seismic behavior of columns that failed in flexure. The main variables are the corrosion levels of reinforcement and applied axial force ratios. The seismic performance of test specimens was assessed in terms of crack pattern, hysteretic response, yield displacement, lateral loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Firstly, a selected column is simulated with two methods to show the importance of shear response consideration in modeling the seismic behavior of corroded columns. This column is C3 from the tests by Vu and Li (2018a). It was originally ductile-designed but failed in a non-ductile manner due to corrosion.…”
Section: Simulation Without and With Shear Deformation And Comparisonmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, a selected column is simulated with two methods to show the importance of shear response consideration in modeling the seismic behavior of corroded columns. This column is C3 from the tests by Vu and Li (2018a). It was originally ductile-designed but failed in a non-ductile manner due to corrosion.…”
Section: Simulation Without and With Shear Deformation And Comparisonmentioning
confidence: 99%
“…Recent studies (Li et al 2018;Vu and Li 2018a) have shown that the failure mode of ductile-designed columns could shift from flexural to shear if the transverse reinforcement was highly corroded. In fact, transverse reinforcement can corrode more severely in reality as the diameter is smaller and the distance to corrosive environment is closer compared with longitudinal reinforcement (Vu and Li 2018a). Thus, the shear capacity could deteriorate more significantly as compared with flexural capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As chloride ions penetrate through concrete cover and accumulate at the steel surface, corrosion gradually initiates. Expansive corrosion products can further induce cracks and even reduce the shear bearing capacity of components and joint significantly [6][7][8][9][10] (shown in Figure 1). Some key points can be defined based on the mechanisms of corrosion and thus divide the process into different stages [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%